Differencesin Variations of Qira'at al-Sab' Tariq al-Shatibiyyah in Usul al-Qira'at based on verses 1-31 in Surah al-Baqarah - M. Jismani Yusoff; Nor Hafizi Yusof; Ismail Abd Halim (Rabbanica: Journal of Revealed Knowledge)
Learning Qira'at al-Sab' Tariq al-Shatibiyyah is the foundation of the study of the science of Qira'at. This is due to the recitation, and the source is only available through one tariq. Therefore, the focus of this study is analysing the difference in the variation of Qira'at al-Sab' based on Tariq al-Shatibiyyah in Usul al-Qira'at based on verses 1-31 of Surah al-Baqarah and it does not involve Tariq Tayyibat al-Nashr which includes various tariqs. This study was conducted based on a qualitative research approach. It focused on the differences in manhaj in Usul al-Qira'at for the seven popular Qira'at Imams. It involves data collection methods based on library research or documentation studying related materials and documents. The data were analysed based on inductive and deductive approaches. The study of Qira'at al-Sab' is closely associated with the variety of recitations of the Qur'an that are recognised and practised in the Islamic tradition. Although essential, this field faces several challenges categorised as theoretical, practical, and societal perception problems. The results of the study can help individuals who study the Ilmu Qira'at know the difference between the variations of Qira'at al-Sab' Tariq al-Shatibiyyah in Usul al-Qira'at and then be able to practice it in the verses involved in this study.